Deliverable 6.16 Natural Hazard Assessment in the Arctic - Anne Solgaard; Ahlstrøm, Andreas Peter; Mankoff, Kenneth; Navarro, Francisco; De Andrés, Eva; de Corcuer, María Isabel; Otero, Jaime; Pirazzini, Roberta; Valisuo, Ilona; Hancock, Holt; Rontu, Laura; Shevnina, Elena; et al. (Zenodo, 2021)
This document describes the main body of work carried out in Task 6.4 - Natural hazards in the Arctic. This document is intended to: − Describe the needs of the stakeholders. − Provide a description of the individual studies in the task and how data and methods from the iAOS advances our understanding of the selected hazards. − Discuss which stakeholder needs are met and what is still required in cases where they are not. − Provide input to the INTAROS roadmap based on the work on natural hazards in the Arctic.